2018
DOI: 10.1002/slct.201801556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH of Precursor on Up/Downconversion and Cathodoluminescence of Gd2O3:Ho3+/Yb3+ Phosphor and Magneto‐Optic Studies

Abstract: The effect of pH of precursor solution has studied on structural and up/downconversion emission properties of Ho3+/Yb3+ doped Gd2O3 host synthesized through hydrothermal route. Best sample morphology (rod‐shaped) is found corresponding to the pH value of pH‐9.1 of the precursor solution. Due to the low phonon frequency of Gd2O3 host, intense green upconversion emission around 539, 550 nm wavelength is observed from the sample on 980 nm diode laser excitation. In down conversion emission mode, bands around 539,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…43 The apparent absorption peaks at 2360 cm À1 and 1630 cm À1 correspond to OQCQO and CQO, respectively, which may be due to the absorption of CO 2 in the air or the incomplete release of CO 2 during the calcinations of Gd 2 O 3 . 44 The absorption peak at 1630 cm À1 is significantly enhanced for Gd 2 O 3 /GQD, which is due to the CQC stretching vibration of GQDs. 45 The relatively weak absorption peak at 1090 cm À1 corresponds to C-O-C and is caused by a small amount of residual organics in the DEG solvent.…”
Section: Resultsmentioning
confidence: 94%
“…43 The apparent absorption peaks at 2360 cm À1 and 1630 cm À1 correspond to OQCQO and CQO, respectively, which may be due to the absorption of CO 2 in the air or the incomplete release of CO 2 during the calcinations of Gd 2 O 3 . 44 The absorption peak at 1630 cm À1 is significantly enhanced for Gd 2 O 3 /GQD, which is due to the CQC stretching vibration of GQDs. 45 The relatively weak absorption peak at 1090 cm À1 corresponds to C-O-C and is caused by a small amount of residual organics in the DEG solvent.…”
Section: Resultsmentioning
confidence: 94%
“…Figure 6 a shows the photoluminescence excitation (PLE) spectra of the yHo 3+ (where y = 1.0, 3.0 & 5.0 mol %) doped CaTiO 3 phosphors in the spectral region of 300–500 nm with λ em fixed at 547 nm (corresponding to the 5 S 2 → 5 I 8 transition of Ho 3+ ion). The spectra contain intense excitation peaks at 362, 419, 452 and 486 nm and they are assigned due to 5 I 8 → 3 H 5, 5 I 8 → 5 G 5 , 5 I 8 → 5 G 6 and 5 I 8 → 3 F 3 transitions of Ho 3+ ions, respectively 3 , 46 . The excitation peak at 452 nm due to 5 I 8 → 5 G 6 transition appears with maximum intensity.…”
Section: Resultsmentioning
confidence: 99%
“…This again conrms the presence of high-impurity bands in the sample. 31,32 In the 1500 °C annealed sample, it was observed that the percentage transmittance values of these bands are much less. The lower transmission values are evidence that the sample purity is very high.…”
Section: Ftir Analysismentioning
confidence: 98%